Identifying of Elementary Students’ Mental Model on Gravity Concept - Neni Hermita, Tengku Aci Parlina, Zerta Hainul Putra, Mahmud Alpusari, Jesi Alexander Alim, Intan Kartika Sari, Eva Astuti Mulyani, Riki Apriyandi Putra, Khoiro Mahbubah, Subuh Anggoro, Andi Suhandi (International Journal of Advanced Science and Technology, 2020)
This study aims to analyze fourth grade elementary school students’ mental models on gravity concept in one of elementary school in Pekanbaru, Indonesia. The method in this study was descriptive quantitative research methods with instruments test in the form of an understanding level test which is divided into three concepts, the subjects in this study consisted of 34 students. The results showed that students’ mental model related to gravity concept 11.76% of students categorized the scientific mental model on the first concept in level understanding test, the highest average was obtained by the synthetic mental model 79.41% in second concept, and there was a drastic increase in the initial mental model in third concept by 55.88%. Understanding of students is based on daily life experiences, but participants can reason according to several components of scientific concepts. So that a reconstruction of learning is needed that can connect the experience of students with the concepts to be learned.Keywords: mental model, gravity concept, fourth elementary students.